Global applications of pervasive and ubiquitous computing - Gao, Tao, 1981-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book provides the global perspective and efforts in building and applying pervasive and ubiquitous computer technology"--Provided by publisher.
Design and implementation of the embed computer based on CompactPCI express bus / Feng Guo ... [et al.] -- Niche genetic algorithm based on sexual reproduction and multimodal function optimization problem / Yulong Tian ... [et al.] -- Coordination performance evaluation of supply logistics in JIT environment / Guo Li ... [et al.] -- The WiMap: a dynamic indoor WLAN localization system / Junjun Xu ... [et al.] -- A novel design of motion detector using mouse sensor / Boning Zhang ... [et al.] -- Identifying disease genes based on functional annotation and text mining / Fang Yuan, Mingliang Li, Jing Li -- TB-WPRO: title-block based web page reorganization / Qihua Chen, Xiangdong Wang, Yueliang Qian -- Constructing the collaborative supply logistics operation mode in assembly system under JIT environment / Guo Li, Tao Gao, Lun Ran -- Construction competitiveness evaluation system of regional biopharma industry and case study: taking Shijiazhuang as an example / Bing Zhao, Dong Sheng Zhang, Yong Zheng Zhao -- Development of intellectual property of communications enterprise and analysis of current situation of patents in emerging technology field / Wenjia Ding -- Image fusion of ECT/ERT for oil-gas-water three-phase flow / Lifeng Zhang -- Modern educational technique center educational media management based on design and practice of questionnaire / Hou Jie -- Residential load pattern analysis for smart grid applications based on audio feature EEUPC / Yunzhi Wang ... [et al.] -- The design of portable integration strengthening machine / Li Yuan, Ximing Lu, Ruifang Huang -- The information construction of wind farm based on SIS system / Yao Wan-Ye, Yin Shi -- Beyond 3G techniques of orthogonal frequency division multiplexing and performance analysis via simulation / Chunyan Wang -- Dynamic spectrum auction and load balancing algorithm in heterogeneous network / Yan Jiang -- A novel detection method of paper defects based on visual attention mechanism / Ping Jiang, Tao Gao -- Research and implementation of self-publishing website platforms for universities based on CMS / Liu Chong, Wang Mei, An Wen Guang -- Dynamic and secure business data exchange model for SaaS-based collaboration supporting platform of industrial chain / Shuying Wang, Jizi Li, Shihua Ma -- 3-D video based disparity estimation and object segmentation / Tao Gao -- Design and implementation of bipolar digital signal acquisition and processing system based on FPGA and ACPL-224 / Guangfu Lin, Zhenxing Yin, Guo Feng -- Financial distress prediction of Chinese-listed companies based on PCA and WNNs / Xiu Xin, Xiaoyi Xiong -- Highway background identification and background modeling based on projection statistics / Jun Zhang -- Method of measuring the switching time of dual redundant NIC / Zhengrong Tao, Zhenxing Yin -- Modeling of across-chain network dynamic competition for MNC in industrial cluster / Chunling Liu ... [et al.] -- Comprehensive structure of novel voice priority queue scheduling system model for VoIP over WLANs / Kashif Nisar, Angela Amphawan, Suhaidi B. Hassan.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed December 17, 2012).
Keywords: Ubiquitous computing; Human-computer interaction; Smart grid applications; Pervasive computing environments; Architecture development; Software development; Information systems; Electronic books